Pengaruh Akuntansi Keprilakuan terhadap Budgetary Slack yang di Mediasi oleh Religiusitas - M. Farhan Hadi Yuliani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Budgetary slack remains a critical issue in organizational financial management, often influenced by human behavior and individual values. This study aims to determine the influence of behavioral accounting on budgetary slack, with religiosity serving as a mediating variable. This research applies a quantitative approach to analyze the behavioral dynamics within financial planning. The sampling technique used was saturated sampling, collecting data through questionnaires distributed to all employees of CV. Abadi Consultant. The collected data was then analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) supported by SmartPLS software. The results of the study indicate that behavioral accounting and religiosity significantly affect budgetary slack. Behavioral accounting also positively affects religiosity. However, religiosity is not able to mediate the influence of behavioral accounting on budgetary slack. The implication of this study suggests that CV. Abadi Consultant should consider character-based recruitment and ethical or moral training to build organizational commitment, reinforce integrity, and prevent opportunistic budget manipulation